P260 Working conditions and health of minas gerais court workers, brazil: a longitudinal study (justicel-mg). (1st September 2016) - Costa, Bruna; Lima, Eduardo; Assunção, Ada
Abstract : The Brazilian judiciary system is being changed. Technological innovations and new management practices are in progress in order to obtain a greater efficiency in serving the population. Nevertheless, this new context has costs for the Court workers. The present report aims to describe the development of a longitudinal study about labour conditions and health status in Minas Gerais State Court, Brazil. All permanent workers (N = 12, 215) allocated in the 296 Minas Gerais law districts was eligible. Ineligibility criteria were pregnancy, vacation and sick leave during the data collection phase. Data was collected by phone; the first wave was in 2016, the second one will be realised in 2017. The estimation of the sample size (n = 1370) considered the following parameters: number of workers, prevalence of sick leave of 40% and 95% confidence interval. A stratified proportional random sampling was performed; the variables considered for stratification were function, law district, age and sex. Five groups of outcomes were developed: 1) life habits, including food consumption, physical activity, and smoking; 2) nutrition status, measured as self-reported weight and height (body mass index); 3) mental health (psychiatric medication use and sleep problems); 4) chronic diseases; and 5) sick leave. Regarding organisational risk factors, we assessed environmental conditions, psychological harassment, job demands, work control, social support, reward and exposure to technological innovation (electronic tools use). Sociodemographic and job characteristics were also controlled for future analysis. The longitudinal follow-up will allow us to detect risk and protective factors for general health among Minas Gerais Court workers. The results will be useful to support health policies in the Brazilian judiciary sector.